Immunomodulatory regulator blockade in a viral exacerbation model of severe asthma - Nicholas, Ben; Lee, Hyun-Hee; Guo, Jane; Cicmil, Milenko; Blume, Cornelia; Malefyt, René De Waal; Djukanović, Ratko (Frontiers in Immunology, 2022)
Asthmatics are more susceptible to viral infections than healthy individuals and are known to have impaired innate anti-viral defences. Influenza A virus causes significant morbidity and mortality in this population. Immuno-modulatory regulators (IMRs) such as PD-1 are activated on T cells following viral infection as part of normal T cell activation responses, and then subside, but remain elevated in cases of chronic exposure to virus, indicative of T cell exhaustion rather than activation. There is evidence that checkpoint inhibition can enhance anti-viral responses during acute exposure to virus through enhancement of CD8+T cell function. Although elevated PD-1 expression has been described in pulmonary tissues in other chronic lung diseases, the role of IMRs in asthma has been relatively unexplored as the basis for immune dysfunction. We first assessed IMR expression in the peripheral circulation and then quantified changes in IMR expression in lung tissue in response to ex-vivo influenza infection. We found that the PD-1 family members are not significantly altered in the peripheral circulation in individuals with severe asthma but are elevated in pulmonary tissues following ex-vivo influenza infection. We then applied PD-1 Mab inhibitor treatment to bronchial biopsy tissues infected with influenza virus and found that PD-1 inhibition was ineffective in asthmatics, but actually increased infection rates in healthy controls. This study, therefore, suggests that PD-1 therapy would not produce harmful side-effects when applied in people with severe asthma, but could have important, as yet undescribed, negative effects on anti-viral responses in healthy individuals that warrant further investigation.